22.1: Invited Paper: New Fluorescent Blue Host Materials for Achieving Low Voltage in OLEDs. Issue 1 (June 2015) - Okinaka, Keiji; Ikeda, Takeshi; Mitsuya, Masayuki; Saito, Hiroyuki; Ito, Hirokatsu; Kawamura, Masahiro; Kuma, Hitoshi
Abstract : New fluorescence blue host (BH) materials for achieving low voltage have been developed. Low efficiency and short lifetime were main issues to reduce operation voltage when using former generation blue hosts. Therefore new molecular structure of BH was designed to improve both electron and hole mobility and optimize ionization potential (IP) for overcoming the issues. New BHs showed lower voltage and comparable lifetime than former generation BHs. Furthermore, as a result of device optimization using the new BH, low voltage of 3.0V with a high current efficiency of 7.23cd/A, CIE‐y of 0.053 at 10mA/cm 2 was successfully achieved in a top‐emission device.